2004
DOI: 10.1111/j.1365-2958.2004.04027.x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of fibronectin‐mediated bacterial adherence to host cells

Abstract: SummaryMany pathogenic Gram-positive bacteria produce cell wall-anchored proteins that bind to components of the extracellular matrix (ECM) of the host. These bacterial MSCRAMMs (microbial surface components recognizing adhesive matrix molecules) are thought to play a critical role in infection. One group of MSCRAMMs, produced by staphylococci and streptococci, targets fibronectin (Fn, a glycoprotein found in the ECM and body fluids of vertebrates) using repeats in the C-terminal region of the bacterial protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
191
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(199 citation statements)
references
References 77 publications
7
191
0
1
Order By: Relevance
“…In the case of S. suis, it has been demonstrated recently that S. suis adhesion to and intracellular invasion of PBMEC increases more than 500 and 700 %, respectively, when bacteria are precoated with fibronectin (Vanier et al, 2007a). Although the mechanisms by which fibronectin-binding proteins trigger the internalization of bacteria by mammalian cells are not completely understood, it has been suggested that binding of fibronectin to a host integrin might initiate a complex cascade of cell signalling that leads to reorganization of cytoskeletal components and consequent internalization of the bacteria (Schwarz-Linek et al, 2004). Accordingly, S. suis invasion of endothelial cells is actin-dependent (Vanier et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of S. suis, it has been demonstrated recently that S. suis adhesion to and intracellular invasion of PBMEC increases more than 500 and 700 %, respectively, when bacteria are precoated with fibronectin (Vanier et al, 2007a). Although the mechanisms by which fibronectin-binding proteins trigger the internalization of bacteria by mammalian cells are not completely understood, it has been suggested that binding of fibronectin to a host integrin might initiate a complex cascade of cell signalling that leads to reorganization of cytoskeletal components and consequent internalization of the bacteria (Schwarz-Linek et al, 2004). Accordingly, S. suis invasion of endothelial cells is actin-dependent (Vanier et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This highly conserved segment occurs once in the most C-terminal FnBRs of FnBPs, with the exception of FnBPA and FnBPB from S. aureus and FnZ from Streptococcus equisimilis (7). Potentially, several copies of Fib1 can be bound to the FnBR region of FnBPs (11).…”
Section: Discussionmentioning
confidence: 99%
“…1A) (8 -10). The FnBRs of SfbI are homologous to tandem repeats in FnBPs of other streptococci and Staphylococcus aureus, and new boundaries for FnBRs of both streptococci and staphylococci have recently been suggested based on structural data (7,11). FnBRs are intrinsically disordered and undergo a conformational change on binding to Fn (12)(13)(14).…”
mentioning
confidence: 99%
“…Previous studies have shown that various Gram-positive bacteria express multiple receptors that bind to fibronectin and have a critical role in the infectious process [21]. However, information highlighting what role fibronectin binding by S. mutans plays in the pathogenesis of infective endocarditis is sparse.…”
Section: Discussionmentioning
confidence: 99%